The Implementation of Ecoliteracy as a Learning Resource to Improve Environmental Care Attitudes in Elementary Schools - Misbahudholam AR, Muhammad; Sama', Sama'; Aini, Kurratul (Universitas Pendidikan Indonesia, 2023)
Ecoliteracy refers to learning outside the classroom by utilizing the surrounding environment as a learning resource. This study aimed to determine the steps for implementing ecoliteracy with nature as a learning resource in improving environmental care attitudes in elementary schools. This study employed classroom action research, involving 20 fourth-grade students as participants. This study was divided into two cycles, each of which comprised four stages. The instruments used in the study were the student's environmental care attitude observation sheet and environmental care attitude sheet, and the teacher's activity sheet. The findings revealed that the caring attitude towards the environment reached an average of 61%; 14 students (70%) were in the caring category and six students (30%) in the very caring category. The learning outcomes of Cycle 1 were four students (20%) who passed and 16 students (80%) who failed. The attitude of caring for the environment in the Cycle 2 increased following the implementation of ecoliteracy learning steps, as indicated by the questionnaire results that one student (5%) was in the caring category, and 19 students (90%) in the very caring category. Meanwhile, the learning outcomes obtained in the Cycle 2 were 15 students (75%) in the complete category and five students (15%) in the incomplete category.